2019
DOI: 10.1200/jco.2019.37.15_suppl.e18109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical responses and survival in Hispanic patients with non-small cell lung cancer treated with immunotherapy compared with non-Hispanic whites.

Abstract: e18109 Background: The main immunotherapy (IMMUNO) trials that led to the approval of these agents for non-small cell lung cancer (NSCLC) accrued a minimum number of Hispanic (HISP) patients (pts) or, in some studies, no HISP pts at all. Additional data is thus needed to validate outcomes in HISP pts with NSCLC treated with IMMUNO. While it is known that genomic profiles and cancer survivals are different between HISP, Non-Hispanic Whites (NHW), and African-Americans; no study has yet looked at differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Likewise, if we consider the main outcomes to immunotherapy in NSCLC, most of the CheckMate and KEYNOTE trials were done in the United States and Europe, and they did not include or included a minimal number of Hispanics. Recently, Raez et al 25 reported information from 256 Hispanic patients with NSCLC treated with immunotherapy (mainly as second-line therapy) in Argentina, Peru, and the United States (Miami). In parallel, the authors matched these data with 180 NHW controls, finding no difference in outcomes (progression-free survival [PFS] and overall survival [OS]) at 4 and 22 months.…”
mentioning
confidence: 99%
“…Likewise, if we consider the main outcomes to immunotherapy in NSCLC, most of the CheckMate and KEYNOTE trials were done in the United States and Europe, and they did not include or included a minimal number of Hispanics. Recently, Raez et al 25 reported information from 256 Hispanic patients with NSCLC treated with immunotherapy (mainly as second-line therapy) in Argentina, Peru, and the United States (Miami). In parallel, the authors matched these data with 180 NHW controls, finding no difference in outcomes (progression-free survival [PFS] and overall survival [OS]) at 4 and 22 months.…”
mentioning
confidence: 99%
“…If we consider the outcomes to immunotherapy in NSCLC, most of the registration trials were done in the United States and Europe, and they did not include anybody or enrolled a minimal number of Hispanics. Raez et al 36 reported data from 256 Hispanics with NSCLC treated with single-agent immunotherapy as second-line in LATAM and the United States. These data were compared with 180 NHW controls, finding no difference in outcomes (PFS and OS).…”
Section: Gene Expression Profilementioning
confidence: 99%